Knowledge of Quadriceps Angle (Q-ANGLE) among Physiotherapy students - Tay, Yu Xin (2024)
Background A foundational understanding of musculoskeletal parameters, including the Quadriceps angle (Q-angle) is required in physiotherapy education for optimal clinical practice, as it plays a crucial role in assessing lower-limb alignment and biomechanics. Despite its clinical value, there is a significant gap in the existing literature regarding physiotherapy students' knowledge of the Q-angle and their ability to apply it in clinical settings. This study aims to address this gap by investigating the knowledge level of the Q-angle among physiotherapy students at Universiti Tunku Abdul Rahman (UTAR). By identifying students’ obstacles, this research intends to provide insights that may be used to improve educational practices, ensuring future physiotherapists in Malaysia have the essential abilities to thrive in musculoskeletal rehabilitation.